Strategies of speed increase during V2 skating technique in elite cross-country skiers - Ohtonen, O.; Linnamo, V.; Lindinger, S. J. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
V2 skating is one of the most commonly used skating techniques which nowadays is applied in a wide range of terrains from flat surfaces to moderate and even steep uphill sections. Some studies have investigated the speed control of the V2 technique from kinematic (e.g. Nilsson, 2004) and from kinematic together with pole kinetic (e.g. Millet 1998) perspective but fully combined approach with these two methods including also leg kinetics and wider speed scale is missing. The aim of the present study was to examine how skiers control their speed with V2 skating technique and whether there is a certain strategy for it.